Variation in spirometry parameters in children with and without recurrent respiratory problems - Gauchan, Eva; BK, Ganesh; Koirala, Deepak Prasad (Journal of Kathmandu Medical College, 2020)
Background: Children having recurrent episodes of respiratory symptoms account for a major source of hospitalization. These children have increased morbidities and if not identified in time can have impaired lung function as adults. Objectives: The aim of our study was to compare the spirometry parameters and bronchodilator reversibility in children with and without recurrent respiratory problems.Methodology: This was a prospective observational study conducted in the Pediatric department of Manipal Teaching Hospital comparing 35 children with recurrent respiratory problems and 35 children with no history of recurrent respiratory problems. After thorough instructions, baseline spirometry was done in all children and recordings were noted. Thereafter they were given two puffs of salbutamol (100 µg) and repeat testing was done 20 minutes later. Bronchodilator reversibility was calculated according to standard formula. Various statistical tests were used to compare the findings between the two groups.Results: The recurrent respiratory problem group had 31 (88%) cases of bronchial asthma, two (5.7%) bronchiolitis obliterans, one (2.8%) pulmonary eosinophilia, and one (2.8%) common variable immunodeficiency syndrome. The median values of FEV1 (p=